2016
DOI: 10.1002/eat.22506
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis on the longitudinal relationship between eating pathology and depression

Abstract: Los resultados del meta-análisis mostraron que la alimentación patológica era un factor de riesgo para depresión (rm=0.13) y que la depresión era un factor de riesgo para la alimentación patológica (rm=0.16). Los análisis de meta-regresión mostraron que estos efectos eran significativamente más fuertes para estudios que operacionalizaban la alimentación patológica como un diagnóstico de trastorno de la conducta alimentaria versus síntomas de alimentación patológica, y para los estudios que operacionalizaban la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
108
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(121 citation statements)
references
References 87 publications
(136 reference statements)
8
108
1
4
Order By: Relevance
“…For instance, recent research has shown that 60% of individuals with BN met criteria for a lifetime major depressive disorder (Godart et al, 2015), and early research that compared individuals with BN to individuals with major affective disorder reported comparable levels of depressive symptoms across both conditions . Indeed, depressive symptoms have been shown to predict short-and long-term BN persistence, poor treatment outcome, and relapse (Fahy & Russell, 1993;Keski-Rahkonen et al, 2013;Puccio et al, 2016;Vall & Wade, 2015), which suggests that depressive symptoms in BN should be an important target for treatment. Indeed, depressive symptoms have been shown to predict short-and long-term BN persistence, poor treatment outcome, and relapse (Fahy & Russell, 1993;Keski-Rahkonen et al, 2013;Puccio et al, 2016;Vall & Wade, 2015), which suggests that depressive symptoms in BN should be an important target for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, recent research has shown that 60% of individuals with BN met criteria for a lifetime major depressive disorder (Godart et al, 2015), and early research that compared individuals with BN to individuals with major affective disorder reported comparable levels of depressive symptoms across both conditions . Indeed, depressive symptoms have been shown to predict short-and long-term BN persistence, poor treatment outcome, and relapse (Fahy & Russell, 1993;Keski-Rahkonen et al, 2013;Puccio et al, 2016;Vall & Wade, 2015), which suggests that depressive symptoms in BN should be an important target for treatment. Indeed, depressive symptoms have been shown to predict short-and long-term BN persistence, poor treatment outcome, and relapse (Fahy & Russell, 1993;Keski-Rahkonen et al, 2013;Puccio et al, 2016;Vall & Wade, 2015), which suggests that depressive symptoms in BN should be an important target for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Depression has been found to predict obesity in some studies (19; 20), potentially due to its association with disordered eating behaviors (21). There is also evidence that depressive symptoms reduce individuals’ capacity to cope with life stressors (22; 23).…”
Section: Introductionmentioning
confidence: 99%
“…First, given evidence that depression is associated with multiple aspects of eating disorder psychopathology (e.g., Jordan et al, 2009; Spoor et al, 2006; Puccio et al, in press), it was hypothesized that depressive symptoms would be independently associated with all eating disorder symptom variables. Second, consistent with evidence that variability in affect commonly precipitates (increases in negative affect, decreases in positive affect) and follows (decreases in negative affect, increases in positive affect) binge eating and purging behaviors (e.g., Engel et al, 2013; Smyth et al, 2007), it was hypothesized that affect lability would emerge as the most salient predictor for binge eating and self-induced vomiting.…”
Section: Introductionmentioning
confidence: 99%
“…Third, given the association between perfectionism and obsessive-compulsive symptoms (e.g., Rheaume et al, 1995), as well as prior research suggesting an association between perfectionism and rituals/preoccupations (e.g., Halmi et al, 2000), it was hypothesized that maladaptive perfectionism would emerge as the most salient predictor for eating disorder rituals and preoccupations. Finally, in light of prior evidence linking dietary restraint and restriction to perfectionism and the various affective constructs examined here (e.g., Engel et al, 2005; Jordan et al, 2009; McLaren et al, 2001; Puccio et al, in press), it was hypothesized that all of the predictor variables would be independently associated with dietary restraint.…”
Section: Introductionmentioning
confidence: 99%